Comparing Vector-Borne Disease Surveillance and Response in Beijing and the Netherlands. Issue 1 (26th July 2022) - Onstwedder, Charlotte; Lock-Wah-Hoon, Jerome; van Dorp, Sigrid; Braks, Marieta; van Asten, Liselotte; Zheng, Yang; Krafft, Thomas; Tong, Ying; van der Hoek, Wim; Liu, Qi-Yong; Pilot, Eva; Wang, Quanyi; et al.
Background: Climate change, environmental change, and globalization affect the geographical distribution of vector-borne diseases. Temperate regions should be prepared for emerging diseases and learn from each other's experiences. Objective(s): The vector-borne disease preparedness in two regions, Beijing and the Netherlands, were compared in order understand their similarities and differences leading to learning points on this complex topic. Methods: A comparative study was performed using interviews with vector-borne disease experts from Beijing and the Netherlands and supplemented by literature. Findings: In Beijing, syndromic surveillance is a priority for the identification of suspected vector-borne disease cases. In the Netherlands, the main surveillance emphasis is on laboratory confirmed vector-borne disease cases. Vector-surveillance at potential points of entry and other high-risk locations is performed according to the International Health Regulation (2005) in both settings. Beijing controls invasive and native mosquitos, which is not the case in the Netherlands. In Beijing, vector surveillance is performed to measure mosquito density around hospitals, this is not observed in the Dutch setting. Health risks posed by ticks are a priority in urban areas in the Netherlands, and the public is educated in self-protection. In contrast, ticks seem to occur less often in Beijing's urban areas. Conclusions: The vector-borne disease context framework allowed us to compare the vector-borne disease preparedness between Beijing and the Netherlands, despite differences in vector-borne disease challenges. We can learn valuable lessons concerning surveillance and early detection of emerging vector-borne diseases when comparing the preparedness between different regions.